301 Older Farmers' Experiences of Musculoskeletal Disorders. (16th September 2019) - Cunningham, John; Kerin, Austin; Galvin, Rose; Robinson, Katie
Abstract: Background: Almost a third (n=41, 000) of all Irish farm holders are aged 65 years or older. Older farmers are vulnerable to Musculoskeletal Disorders (MSD's) both by virtue of the nature of their work and their age. MSD's are a known risk factor for workplace accidents and farming is the highest risk occupation in Ireland. This study aimed to explore older farmers' experiences of living with and accessing healthcare for MSD's. Methods: A qualitative study design employing semi-structured interviews was employed. Nine Irish farmers aged 65 years and over with current or previous experience of MSD's were recruited. All participants continued to farm on either a full-time or part-time basis. Data were analysed using thematic analysis. Results: Four themes describing older farmers' experiences of MSD's and healthcare were identified; (1) acceptance of MSD's as inevitable (2) biomechanical and biological beliefs about MSD's (3) resilience and a commitment to continuing work in response to MSD's (4) scepticism and avoidance of healthcare. Conclusion: To the best of our knowledge this is the first qualitative study of older Irish farmers' experiences of MSD's. Findings reveal that older farmer's experiences differ significantly from those reported by other occupational groups. Commitment to continue working permeated the findings of this study and shaped older farmers' experiences and responses to MSD's. Older farmers accept MSD's and pain as inevitable consequences of farming, and they respond to MSD's with stoicism. Lack of healthcare provider knowledge about farming culture and practices contributes to older farmers' negative healthcare experiences and avoidance of healthcare. Given the prevalence of MSD's in this population future research should focus on developing and evaluating appropriate health promoting and patient-centered interventions to support continued safe farming for older Irish farmers.